1993
DOI: 10.1097/00001888-199303000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Problem effectiveness in a course using problem-based learning

Abstract: The students' learning activities covered an average of 64% of the intended course content; in addition, the students generated learning issues not expected by the faculty, and half of these issues were judged relevant to the course content. Thus, PBL seems to permit students to adapt learning activities to their own needs and interests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 0 publications
6
52
0
Order By: Relevance
“…95212;Fax: 95148;E-mail: haqwia@ksau-hs.edu.sa;alhaqwi@gmail.com Students, under the guidance of a tutor, conduct the PBL sessions according to predetermined process. This process involves clear role for every members of the group, known steps of discussion, and concluding learning objectives from the discussed problem (Dolmans et al 1993(Dolmans et al , 2001.…”
Section: Practice Pointsmentioning
confidence: 99%
“…95212;Fax: 95148;E-mail: haqwia@ksau-hs.edu.sa;alhaqwi@gmail.com Students, under the guidance of a tutor, conduct the PBL sessions according to predetermined process. This process involves clear role for every members of the group, known steps of discussion, and concluding learning objectives from the discussed problem (Dolmans et al 1993(Dolmans et al , 2001.…”
Section: Practice Pointsmentioning
confidence: 99%
“…Students can become angry and confused when the facilitator does not provide enough information (Alavi 1995). Alternatively, too much intervention can be stifling for the students, leading to discrepancies between the learning objectives identified by students and the recommendations made by the tutor (Dolmans et al 1993). Frost (1996) outlined the role of the facilitator in the tutorial group to encourage the students to explore and reflect on existing knowledge to develop learning objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown no difference and sometimes lower content knowledge scores for PBL students. Students exhibit gaps in their knowledge base created by PBL activities that do not cover all the required course content [31,32]. PBL has not gained significant popularity in engineering due to concerns over content knowledge gaps as well as the large time scale necessary to solve a significant engineering problem [33].…”
Section: Problem-based Learning In Undergraduate Engineering Educationmentioning
confidence: 99%